Promoting Citizenship Education through Collaborative Groups of School Leaders - Karadimou, Maria; Tsioumis, Kostis (International Journal of Learning and Development, 2024)
The purpose of this study is to examine whether there is a correlation between the leader's collaborative networks (teachers, students, and the community) and the civic education provided to students in their school unit. The survey was conducted in July 2020 using a closed questionnaire. The research involved 122 primary school teachers (kindergarten teachers, teachers, and expertise teachers) who were asked to choose from a five-point scale, or from multiple answers. The survey based on the assumption that the existence of a collective and democratic climate of school administration helps to encourage teachers to address issues of education in the capacity of citizen. The results of the survey lead us to confirm our initial thought, which was the springboard for conducting this research, that those teachers who work in an environment characterised with respect and collectivity, it makes sense to be them who embrace the principles of citizenship education and consider it important to convey them on to their students.